Pengaruh Sistem Keuangan Desa dan Kompetensi Sumber Daya Manusia Terhadap Akuntabilitas Pengelolaan Dana Desa Studi pada Desa-Desa di Kecamatan Telaga Kabupaten Gorontalo Provinsi Gorontalo - Amir Yunus; Harun Blongkod; Victorson Taruh (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of the Village Financial System (Siskeudes) and human resource competence on the accountability of village fund management. The study was conducted in villages within the Telaga Subdistrict, Gorontalo Regency, Gorontalo Province, employing a quantitative method. Data was collected through questionnaires. The analysis techniques included validity testing, reliability testing, and descriptive analysis. Data collection employed purposive sampling, or sampling with specific criteria, namely villages that have already implemented the Siskeudes application, with a total sample of 120 respondents across nine different villages: Bulila, Mongolato, Luhu, Hulawa, Dulohupa, Pilohayanga, Pilohayanga Barat, Dulamayo Selatan, and Dulamayo Barat, located in Telaga Subdistrict. The data analysis technique employed in this study was Structural Equation Modeling (SEM), which was conducted using the AMOS 24 program. The results of this study show that the village financial system has an influence on the accountability of village fund management. In contrast, human resource competence does not have an influence on the accountability of village fund management. However, both independent variables simultaneously contribute significantly to the accountability of village fund management.